Between thinking and action: Arendt on conscience and civil disobedience. (December 2016) - Petherbridge, Danielle
Within contemporary debates on civil disobedience, Hannah Arendt's work offers an alternative to both moral and legal approaches by offering a political view of disobedience based on what she terms a principle of dissent at the heart of constitutional democracies. In this sense, she separates disobedience from the moral claims of individual conscience as well as the restrictions imposed by legalistic conceptions. In this article, I first consider Arendt's views on conscience and the arguments she makes for a Socratic notion of conscience understood as a by-product of thinking, as well as her arguments against conscience-based versions of disobedience such as that developed by Kimberley Brownlee. Second, I consider Arendt's defence of a political notion of disobedience and her arguments against legal approaches such as those advocated by John Rawls and William Scheuerman.